2001
DOI: 10.1046/j.1528-1157.2001.26000.x
|View full text |Cite
|
Sign up to set email alerts
|

Study on Photo‐Pattern Sensitivity in Patients with Electronic Screen Game–Induced Seizures (ESGS): Effects of Spatial Resolution, Brightness, and Pattern Movement

Abstract: Summary:  Purpose: With the ever‐increasing popularity of computers, electronic screen game–induced seizure (ESGS) is beginning to pose a serious social problem. To elucidate the pathophysiology of ESGS, with the ultimate goal of prevention, we have been studying photo‐pattern sensitivity in detail with a pattern‐stimulation test using a CRT (cathode ray tube) display. This method is referred to as the “CRT‐pattern test.” Methods: We studied 17 patients brought to our department for evaluation of ESGS. EEG re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Video display units (VDUs) should be less likely than TVs to provoke seizures, because VDUs tend to be smaller, less bright, usually refresh at 70 Hz, as opposed to 50 or 60 Hz, and they do not have the interlaced double raster scan that provides a flicker at half of the scan frequency (113). However, video display computer screens still can produce photic seizures in the sensitive subject (113). A PPR is to be expected among most patients who have a seizure while watching TV.…”
Section: Seizures From Televisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Video display units (VDUs) should be less likely than TVs to provoke seizures, because VDUs tend to be smaller, less bright, usually refresh at 70 Hz, as opposed to 50 or 60 Hz, and they do not have the interlaced double raster scan that provides a flicker at half of the scan frequency (113). However, video display computer screens still can produce photic seizures in the sensitive subject (113). A PPR is to be expected among most patients who have a seizure while watching TV.…”
Section: Seizures From Televisionmentioning
confidence: 99%
“…Photosensitive patients should avoid black‐and‐white checkered floor tiles or patterns, stripes, light through window vents, rotating ceiling fans, flashing lights, and sitting <3 m from a TV. Funatsuka and colleagues (113) recommended that pattern‐sensitive individuals avoid the following: (a) geometric patterns, especially stripes occupying much of the display; (b) fine patterns with spatial frequencies >2 cycles/degree; (c) frequencies ∼20 Hz with pattern‐reversal stimulation; (d) patterns with large differences in brightness; and (e) rapid pattern movements. The National Association of Commercial Broadcasters in Japan and Nippon Hoso Kyokai made recommendations for producers of animated programs.…”
Section: Recommendations In the Literaturementioning
confidence: 99%
“…Visual stimuli are by far the most common trigger of these reflex epilepsies (2,3). Either simple visual stimuli such as light or patterns (4,5) or complex visual excitations such as television or video games may trigger visually induced seizures in subjects with television‐ or video game–induced seizures (6,7).…”
mentioning
confidence: 99%
“…Several lines of evidence suggest that photosensitivity (Jeavons et al, 1972; Panayiotopoulos et al, 1972; Harding et al, 1975), pattern sensitivity (Wilkins et al, 1979; Harding et al, 1994; Fylan & Harding, 1997; Funatsuka et al, 2001) and temporal frequency dependence (Harding et al, 1994; Harding & Harding, 1999) play important roles in the generation of PSE. Our previous study (Tobimatsu et al, 1999) demonstrated that PPR is more frequently observed in response to rapid B/R frame changes (temporal frequency, 12 Hz) compared with monochromatic changes in the patients with “Pokemon seizure.” No antagonistic relation exists between red and blue cone impulses in the primary visual cortex (V1) (Livingstone & Hubel, 1984), so B/R inputs result in maximal stimulation of the visual cortex.…”
mentioning
confidence: 99%
“…Several lines of evidence suggest that photosensitivity Panayiotopoulos et al, 1972;Harding et al, 1975), pattern sensitivity (Wilkins et al, 1979;Fylan & Harding, 1997;Funatsuka et al, 2001) and temporal frequency dependence Harding & Harding, 1999) play important roles in the generation of PSE. Our previous study (Tobimatsu et al, 1999) demonstrated that PPR is more frequently observed in response to rapid B/R frame changes (temporal frequency, 12 Hz) compared with monochromatic changes in the patients with "Pokemon seizure."…”
mentioning
confidence: 99%